Semantic stored procedures programming environment and performance analysis - Efremov, Marjan; Zdraveski, Vladimir; Ristoski, Petar; Trajanov, Dimitar (Springer, Berlin, Heidelberg, 2011)
Supporting the idea of the semantic web, we developed a Semantic Stored Procedures (SSP) programming environment for the Oracle11g database, similar to the existing ones, available for the stored procedures in the relational databases. This show-case SSP-environment supports the basic test/store/execute/remove scenarios for sem_match-queries, but is also a quite extensive system. An eclipse plug-in that provides a GUI for these operations and java API which helps programmers to use the SSP-call functionality were released in the package with the Oracle11g SSP-extension. The performances of our system are comparable (much better in most of the cases) with the existing adapters, as shown with the measurements in comparison with the well-known Jena adapter. Thus, a complete development environment for SSP-programming is now available and the semantic query management, as a simple concatenation of strings inside the code, seems to becoming just a forgotten nightmare of our semantic web programmer’s life.
Keywords: Semantic Web, Semantic Database, Stored Procedure, Sem_match, Eclipse Plug-in